Effect of BMSCs overexpressing intelectin-1 on angiogenesis in rats with cerebral infarction - Bo Zhu; Kun Guo; Lei Zha; Zhengli Di; Hongwei Zhao; Le Chang; Naibing Gu (IBRO Neuroscience Reports)
Background: Cerebral infarction (CI) is a common and frequently occurring acute neurological disease in clinical practice, posing a severe threat to human health. CI results from various causes leading to local cerebral tissue ischemia and hypoxia due to vascular occlusion and impaired blood supply, which in turn leads to tissue necrosis and corresponding clinical manifestations of neurological deficits. However, to date, treatment options for cerebral infarction remain limited. Therefore, it is crucial to rapidly establish collateral circulation to compensate for the occluded vessels and restore blood flow perfusion. Objective: To assess the effect of bone marrow mesenchymal cells transfected with intelectin-1 (Itln-1) gene on the angiogenesis and apoptosis of CI. Method: Lentiviral-mediated transfection of the Itln-1 gene into bone marrow mesenchymal stem cells (BMSCs) was performed, followed by intravenous injection into rats with CI through the tail vein. The volume of the CI, capillary density, and apoptotic cells were detected. Results: With the increase of AKT and eNOS phosphorylation levels, BMSCs with overexpression Itln-1 gene could significantly promote angiogenesis and reduce the infarct volume in the ischemic penumbra. Meanwhile, the ratio of Bcl-2/Bax increased, and apoptotic cells decreased. Conclusion: The overexpression of Itln-1 can effectively promote CI angiogenesis and inhibit cell apoptosis than transplantation of Itln-1 gene or MSCS alone